Using Si textured structure to build vertical graphene sharp edges for electron field emission. (3rd May 2019) - Chen, Lei Feng; Yu, Hua; Zhong, Jiasong; Wu, Jun; Su, Weitao
Abstract: The Vertically-orientated graphene (GP) sharp edges can provide a high density of individual field emission sites and a high field emission enhancement factor. In this report, we used a Si textured structure to build the vertical GP field emission edges. Relying on the periodical textured arrays of the Si surface, a large number of vertical sharp edges of GP are formed on the Si substrate during the electrophoretic deposition process. The vertical GP edges on the textured structure of Si shows a low turn-on electric field of 0.43 V −1 μ m −1, a high enhancement factor of 9450, excellent stability behavior and a uniform luminance intensity image. The excellent field emission properties for the vertical edges are explored and discussed in detail. This investigation of the vertical GP edges on a textured Si surface suggests a potential prospect in application in future field electron emission devices.